2015
DOI: 10.1038/onc.2015.61
|View full text |Cite
|
Sign up to set email alerts
|

WIF1 re-expression in glioblastoma inhibits migration through attenuation of non-canonical WNT signaling by downregulating the lncRNA MALAT1

Abstract: Glioblastoma is the most aggressive primary brain tumor in adults and due to the invasive nature cannot be completely removed. The WNT inhibitory factor 1 (WIF1), a secreted inhibitor of WNTs, is systematically downregulated in glioblastoma and acts as strong tumor suppressor. The aim of this study was the dissection of WIF1 associated tumor suppressing effects mediated by canonical and non-canonical WNT-signalling. We found that WIF1 besides inhibiting the canonical WNT pathway selectively downregulates the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 58 publications
2
116
0
1
Order By: Relevance
“…Findings on Wnt5a roles and functions in these tumors are restricted to the observed increased motility in cultured cell lines (25,27). Recently, however, it has been shown that the enhanced migration caused in hGBMs by reduced Wnt inhibitor 1 activity is mediated by Wnt5a (48). We now demonstrated that Wnt5a functions as a master regulator in determining the prototypical invasive glioma potential in hGBMs, particularly, in their TPCs.…”
Section: Discussionmentioning
confidence: 83%
“…Findings on Wnt5a roles and functions in these tumors are restricted to the observed increased motility in cultured cell lines (25,27). Recently, however, it has been shown that the enhanced migration caused in hGBMs by reduced Wnt inhibitor 1 activity is mediated by Wnt5a (48). We now demonstrated that Wnt5a functions as a master regulator in determining the prototypical invasive glioma potential in hGBMs, particularly, in their TPCs.…”
Section: Discussionmentioning
confidence: 83%
“…Up-regulation of MALAT1 facilitates cell proliferation, migration, and invasion in lung cancer, glioblastoma, esophageal squamous cell carcinoma, renal cell carcinoma, colorectal cancer, osteosarcoma, multiple myeloma, gastric cancer, gallbladder cancer. [10][11][12][13][14][15][16][17][18][19][20] In addition, MALAT1 is associated with the malignant status and poor prognosis in glioma and clear cell renal cell carcinoma. 21,22 Finally, the high level of MALAT1 can act as a marker to predict disease progression in colorectal cancer, multiple myeloma, pancreatic cancer, and non-small cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, our laboratory used ChIP-seq assay of TCF4 and STAT3 and data mining of patient cohorts to derive the molecular subtypes of GBM (42). Moreover, the lncRNA MALAT1 has been reported to be regulated in non-canonical WNT/Ca 2þ / signaling (43). In this study, we disclosed that a high level of NEAT1 negatively regulated WNT negative signaling regulation factors (Axin2, ICAT, and GS3KB).…”
Section: Discussionmentioning
confidence: 76%